Regeneration of an electret filter by contact electrification. Issue 8 (22nd January 2021) - Eun, Jakyung; Lee, Hansol; Jeon, Sangmin
Abstract : Contact electrification restores the surface potential of a polypropylene electret filter for face masks and regenerates its filtration efficiency. Abstract : A facile and efficient method for the regeneration of electrostatic potential in electret filters by contact electrification ( i.e., triboelectrification) was developed herein. The efficiency of a commercial polypropylene (PP) electret filter (PEF) for face masks was evaluated for filtration of particulate matter (PM) composed of fine solid dust and liquid droplets containing airborne bacteria (bioaerosol). The efficiency of pristine PEF for filtration of fine dust was 72.4%; however, this decreased to 62.7% following the removal of electrostatic charges in PEF by ethanol treatment. In contrast to fine dust, the bioaerosol (BA) removal efficiency of the filter was not affected by ethanol treatment because micro-sized liquid droplets could not penetrate the hydrophobic PEF surface. The electrostatic potential of PEF was restored or even enhanced by rubbing with Teflon, which exhibited a large triboelectric charge density. The PM removal efficiency of the resulting filter was higher than that of pristine PEF. Importantly, no performance degradation was observed even after 10 regenerations, demonstrating that the disposable filter can be reused to reduce the environmental problems associated with accumulation of waste.